2022
DOI: 10.3390/nu14040852
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nutritional Supplements Based on L-Theanine and Vitamin B6 in Children with Tourette Syndrome, with Anxiety Disorders: A Pilot Study

Abstract: Background: Tourette syndrome (TS) is a neurodevelopmental disorder characterized by tics and co-occurring disorders. It has been suggested that anxiety occurs in 2–45% patients affected by Tourette syndrome. Despite dietary and nutritional factors have been found to affect a range of neurological conditions, no more studies have investigated the relationship between nutritional supplements and tics. Objective: To evaluate the effectiveness of supplementation of both L-Theanine and Vitamin B6 in reducing tics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
3
0
4
Order By: Relevance
“…Além disto, mesmo que disponíveis para o tratamento dos tiques na ST, o uso desses antipsicóticos em crianças e adolescentes podem também estar associados a comprometimento cognitivo, ganho de peso, letargia e discinesia tardia (HUANG et al, 2022;JANKOVIC et al, 2021;KAHL et al, 2021;RIZZO et al, 2022).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Além disto, mesmo que disponíveis para o tratamento dos tiques na ST, o uso desses antipsicóticos em crianças e adolescentes podem também estar associados a comprometimento cognitivo, ganho de peso, letargia e discinesia tardia (HUANG et al, 2022;JANKOVIC et al, 2021;KAHL et al, 2021;RIZZO et al, 2022).…”
Section: Discussionunclassified
“…Ademais, por se tratar também de um estudo preliminar, com pequeno tamanho de amostra, tais fatores devem ser levados em consideração em estudos futuros (HUANG et al, 2022). avaliou a eficácia que a suplementação de L-teanina, um aminoácido, e a vitamina B6 possuem na redução de tiques em jovens com transtorno do tique crônico ou com ST (RIZZO et al, 2022).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The treatment of tics with the addition of certain foods or supplements has also been attempted, such as probiotics, N-acetyl cysteine, and omega-3 fatty acids, but results have generally not shown significant improvements [ 73 , 74 , 75 ]. One open-label study did show improvement in tics in patients given L-Theanine and Vitamin B6 as compared with a control condition of psychoeducation [ 76 ]. Additionally, an open-label study of magnesium and vitamin B6 showed an improvement in children with TS suffering from clinical exacerbations [ 77 ].…”
Section: “Just the Facts Ma’am” What’s The Evidence About What Situat...mentioning
confidence: 99%